Implementasi Manajemen SDM Dalam Menjaga Loyalitas Karyawan Pada Decoration DIA Dan AKU Di Mataram - Oktapia Wahyu Anggraini; Nizar Hamdi; I Gusti Gede Narung (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
The The study analyzed the implementation of Human Resource Management (HRM) in maintaining employee loyalty at Decoration Dia dan Aku in Mataram. The decorative services industry requires employees who are not only competent but also highly loyal, as service quality is directly influenced by workforce involvement and creativity. This research aims to understand how HRM practices are applied and their role in fostering long-term commitment. Using a qualitative case study approach, data were gathered through in-depth interviews, non-participant observation, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, focusing on data reduction, presentation, and conclusion drawing. The results indicate that comprehensive HRM practices, including strategic planning, targeted recruitment, continuous training, systematic performance appraisal, and competitive compensation, contributed significantly to creating a highly conducive and supportive work environment. Employee loyalty is tangibly evident through several key indicators: a notably low turnover rate, long employee tenure (with many staff serving since 2014-2016), and consistently high organizational commitment as expressed in interviews. Key loyalty factors identified were high job satisfaction stemming from a creative atmosphere, fair and timely compensation, strong and positive interpersonal relationships among peers and management, opportunities for continuous learning and skill development, and the application of a participative leadership style that values employee input. This study concludes that a consistent, holistic, and humanistic HRM strategy successfully enhances employee loyalty, which in turn acts as a crucial driver supporting the business's sustainability and growth within the dynamic creative decoration sector in Mataram. The findings provide practical implications for SMEs in creative industries seeking to build long-term retention.